A tunable band gap of the layered semiconductor Zn3In2S6 under pressure. Issue 5 (17th January 2022) - Susilo, Resta A.; Liu, Yu; Sheng, Hongwei; Dong, Hongliang; Sereika, Raimundas; Kim, Bongjae; Hu, Zhixiang; Li, Shujia; Yuan, Mingzhi; Petrovic, Cedomir; Chen, Bin
Abstract : A highly tunable band gap of the layered semiconductor Zn3 In2 S6 under pressure is reported. The change in the band gap is strongly coupled to the variation and transformation of the crystal structure. Abstract : The band gap is an important property of a semiconductor, and a candidate material with a highly tunable band gap under external tuning parameters will offer wider applications in optoelectronic devices and photocatalytic fields. Here, we show that the layered semiconductor Zn3 In2 S6 possesses a band gap that is highly tunable with pressure. In situ optical absorption shows that the band gap unexpectedly widens with pressure up to ∼13 GPa. Sudden gap narrowing then occurs above 14 GPa, which is followed by progressive gap decreases on further compression and the gap finally closes above 20 GPa. Our study, encompassing X-ray diffraction, Raman spectroscopy experiments and theoretical calculations revealed that the selective responses of the different bonds are responsible for the band gap increase in the low-pressure ranges. We show that the pressure-induced irreversible amorphization is responsible for the sudden gap narrowing whereas the semiconductor–metallic transition is related to the amorphous–amorphous transition at high-pressure due to a change in the local coordination number of Zn atoms. This work demonstrates the high tunability of the electronic and optical properties of layered ternary semiconductors under pressure, providing a potential way for wider applications of this class of materials.